2016
DOI: 10.1038/srep36773
|View full text |Cite
|
Sign up to set email alerts
|

Using community analysis to explore bacterial indicators for disease suppression of tobacco bacterial wilt

Abstract: Although bacterial communities play important roles in the suppression of pathogenic diseases and crop production, little is known about the bacterial communities associated with bacterial wilt. Based on 16S rRNA gene sequencing, statistical analyses of microbial communities in disease-suppressive and disease-conducive soils from three districts during the vegetation period of tobacco showed that Proteobacteria was the dominant phylum, followed by Acidobacteria. Only samples from September were significantly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 53 publications
2
67
0
Order By: Relevance
“…Only one OTU classified as Kaistobacter was connected to RS in both HRS and LRS samples. Kaistobacter has been reported to be more prevalent in suppressive soils [18,20,23], and it is a potential PGPR group because it can produce hormone [19]. Co-occurrence network analysis indicated that the RS invasion affected rhizosphere microbe networks, furthermore, the Flavisolibacter with negatively correlated to RS is one important hub bacteria in HRS networks.…”
Section: Discussionmentioning
confidence: 99%
“…Only one OTU classified as Kaistobacter was connected to RS in both HRS and LRS samples. Kaistobacter has been reported to be more prevalent in suppressive soils [18,20,23], and it is a potential PGPR group because it can produce hormone [19]. Co-occurrence network analysis indicated that the RS invasion affected rhizosphere microbe networks, furthermore, the Flavisolibacter with negatively correlated to RS is one important hub bacteria in HRS networks.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we found that the bacteria Bryobacter and Variibacter, as well as fungi Coniochaeta and Metarhizium, were positively related to soil health. According to related reports, these five types of microorganisms are key microbial groups that affect the occurrence of RKN disease (Liu et al 2016, Cao et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Soil-borne diseases are caused by the imbalance in soil ecosystems, such as changes in planting conditions, changes in climate and environment, and changes in treatment measures; hence, understanding the mutual equilibrium relationship between the original soil microorganisms, and balance of soil ecosystems is the key to prevent the disease from continuing to occur and keep the healthy growth of crops (Liu et al 2016). Microbial imbalances in the "plant-soil-microorganism" ecosystem play an important role in the occurrence of diseases (Classen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a dominant bacterial genus, Kaistobacter, which is associated with disease suppressiveness [43] was less abundant in +DR than in −DR, which indicated a higher chance for plants to be infected by pathogen disease under +DR. Kaistobacter is a member of the bacterial community that responds to the availability of easily degradable C compounds, especially plant root exudates [43,44]. Chickpea rhizosphere under −DR assembled more Kaistobacter than wheat (Fig.…”
Section: Taxonomic and Functional Annotationmentioning
confidence: 97%